2013
DOI: 10.1176/appi.ps.201200382
|View full text |Cite
|
Sign up to set email alerts
|

What Do Outpatients With Schizophrenia and Mood Disorders Want to Learn About Their Illness?

Abstract: In regard to educating patients about their illness, there is no one-size-fits-all approach. Health care professionals need to be sensitive to individual learning preferences, which vary and can include group-based approaches. The results have implications for the training of psychiatrists. In particular, psychiatrists need to be equipped to address patients' questions about the cause of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…Despite the high levels of endorsement for the importance of skilled communication to patient care, participants in this study reported low rates of confidence in these communication skills, particularly with respect to prognosis. This is consistent with findings regarding the practice of clinicians [6], their perceptions of their ability [2], and the unmet information needs of patients and family members [7]. It is encouraging to observe the improvements in self-reported confidence, but more importantly to observe increased self-reported confidence in the ability of trainees to critically evaluate their own communication practice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite the high levels of endorsement for the importance of skilled communication to patient care, participants in this study reported low rates of confidence in these communication skills, particularly with respect to prognosis. This is consistent with findings regarding the practice of clinicians [6], their perceptions of their ability [2], and the unmet information needs of patients and family members [7]. It is encouraging to observe the improvements in self-reported confidence, but more importantly to observe increased self-reported confidence in the ability of trainees to critically evaluate their own communication practice.…”
Section: Discussionsupporting
confidence: 88%
“…Patients and families, on the other hand, report significant unmet needs for information [3] and wish to be better informed about their diagnosis [4][5][6]. The majority (>90 %) prefers to receive diagnostic information from their treating psychiatrist [7], although only 50 % on average are told a diagnosis [6,8], with rates varying across different diagnostic groups: highest for anxiety and depression, lowest for first episode schizophrenia, dementia, and personality disorder. Few studies have addressed the communication of prognostic…”
mentioning
confidence: 99%
“…Information seeking is an important aspect of coping with chronic illness (Lambert and Loiselle 2007; Brashers et al 2002) and many patients with bipolar disorder want to learn more (Hallett et al 2013; Giacco et al 2014). The majority of patients with bipolar disorder would prefer to learn about their illness through a face-to-face conversation with their physician, as do patients with other mental and physical illness (Hallett et al 2013; Gaglio et al 2012; Hesse et al 2005; Horgan and Sweeney 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients with bipolar disorder would prefer to learn about their illness through a face-to-face conversation with their physician, as do patients with other mental and physical illness (Hallett et al 2013; Gaglio et al 2012; Hesse et al 2005; Horgan and Sweeney 2010). This is often not feasible due to the large number of questions that will arise over the long term and the limited access to the treating psychiatrist.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with serious mental illness want to learn more about their disease (Giacco et al, 2014;Griffiths and Crisp, 2013;Hallett et al, 2013). For example, patients with bipolar disorder are not satisfied with the information provided about possible medication side effects (Bowskill et al, 2007).…”
Section: Introductionmentioning
confidence: 99%